Acylative kinetic resolution of racemic methyl-substituted cyclic alkylamines with 2, 5-dioxopyrrolidin-1-yl (R)-2-phenoxypropanoate. Issue 4 (10th January 2022) - Gruzdev, Dmitry A.; Vakarov, Sergey A.; Korolyova, Marina A.; Bartashevich, Ekaterina V.; Tumashov, Andrey A.; Chulakov, Evgeny N.; Ezhikova, Marina A.; Kodess, Mikhail I.; Levit, Galina L.; Krasnov, Victor P.
Abstract : ( R )-2-Phenoxypropanoate ester was efficient chiral resolving agent in acylative KR of racemic cyclic alkylamines; highest selectivity was observed for 2-methylpiperidine with predominant formation of ( R, R )-amide, which was confirmed by DFT modelling. Abstract : The diastereoselective acylation of a number of racemic methyl-substituted cyclic alkylamines with active esters of 2-phenoxypropanoic acid was studied in detail. The ester of ( R )-2-phenoxypropanoic acid and N -hydroxysuccinimide was found to be the most selective agent. The highest stereoselectivity was observed in the kinetic resolution of racemic 2-methylpiperidine in toluene at −40 °C (selectivity factor s = 73) with the predominant formation of ( R, R )-amide (93.7% de ). To explain the observed stereoselectivity, DFT modelling of the transition states in the reactions of the title acylating agent with 2-methylpiperidine and 2-methylpyrrolidine was performed. The calculated values were in good agreement with experimental data. It has been demonstrated that the acylation proceeds via a concerted mechanism, in which the addition of an amine occurs simultaneously with the elimination of the hydroxysuccinimide fragment. The high stereoselectivity of the ( R, R )-amide formation is largely ensured by the lower steric hindrances in the transition states as compared to the formation of ( R, S )-amide.